THE USE OF STEVIA SUGAR (Stevia Rebaudiana) IN THE PRODUCTION OF ROBUSTA COFFEE JELLY CANDY (Coffea Canephora) - Khalidah, Shafiyyah Ummu; Sari, Ayu Pravita; Okfrianti, Yenni (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Jelly candies made from robusta coffee and stevia sugar are a creative and healthy snack made from natural ingredients. Because of the nutritional benefits contained in Robusta coffee, which is rich in caffeine, phenols, flavonoids, saponins, tannins, and antioxidants. This snack is suitable for all groups of people. This nutrition can help keep the body healthy and prevent long-term diseases. Known as a natural sweetener, stevia sugar has a sweetness level between 150 and 300 times that of regular sugar, yet it remains safe for diabetics because it can help regulate their blood sugar. This study aims to determine the water content and preference for jelly candies made from a mixture of Robusta coffee (Coffea canephora) and stevia (Stevia rebaudiana). This experiment applies a completely randomized design (CRD). As many as 40 panelists with semi-trained skills to try this product. This study took place from February to April 2025. The hedonic test results show that formula F3 is preferred for its aroma, taste, and texture, while formula F1 is preferred for its color. For water content, the results are 53.53% for F1, 58.41% for F2, and 47.06% for F3, each above the Indonesian national standard for jelly candy. It has been proven that changes in formulation affect color, aroma, and taste, but do not significantly affect texture.